Parental involvement in residential child care: helping parents to provide a secure base - Esther M.W. Geurts; Marc J. Noom; Erik J. Knorth (Scottish Journal of Residential Child Care)
In the Netherlands, about five percent children receive some type of youth care. This is governed by the Youth Care Act, whereby children and parents get support for problems which may arise in the process of child development or parenting. Inadequate parenting is the reason given for admission to residential care in approximately 70 percent of cases (Knorth & Van der Ploeg, 1994). Research demonstrates that it is helpful for a child if parents are actively involved in the youth care process. The Netherlands has facilities called 'multifunctional youth care organisations'. These are organisations which offer a range of services such as non residential care, day-care, and residential care. One such organisation called STEK developed a method called 'Child and Youth Care in Context' (CYC). This method builds on the idea of secure base and ensures that parents maintain the responsibility for the upbringing of their child and that they have a say in arrangements in the youth care process. This paper will present an overview of evidence encouraging family centred approaches, describe the CYC method and outline findings of a study carried out on its effectiveness.